Violence and the Academic Lives of College Students at the Intersection of Race/Ethnicity and Sexual Orientation/Gender Identity - Carmody, Mary D. (Journal of interpersonal violence, 2022)
To ascertain whether sexual and/or gender minority (SGM) students at a Hispanic-serving institution who experience violence are more likely to experience interference with their academic lives when compared to heterosexual, cisgender students, and how this relationship differs by race/ethnicity. Data came from 736 undergraduate students at a university in the Southwestern United States responding to a 2017 Campus Climate Survey. Multivariable logistic regression was conducted on self-identified SGM students and reported interference with their academic lives. The model was also tested for effect modification by race/ethnicity. Two-thirds (67.65%) of SGM students reported four or more incidences of violence. Nearly one-fifth (18.83%) of SGM students reported being harassed, insulted, threatened, or intimidated, and 2.63% reported being physically hurt (including forced sex), because the perpetrator thought the individual might have been gay, lesbian, bisexual, or transgender. SGM students had 2.44 (95% CI: 1.29, 4.61) increased odds of interference with academic life as a result of violence victimization compared with non-SGM students. When the model was evaluated for effect modification by race/ethnicity, large effect sizes were observed, although the results were not significant. SGM undergraduate students are at significantly increased risk of violence and interference with their academic lives. This research emphasizes the need for institutions of higher education to ensure that their policies and practices support equal access to education by SGM students. Additionally, this study contributes insights into a potential protective effect of Hispanic ethnicity that warrants further research.